Decisional needs of patients with recurrent high-grade glioma and their families. Issue 5 (11th June 2022) - Sorensen von Essen, Helle; Stacey, Dawn; Dahl Steffensen, Karina; Guldager, Rikke; Rom Poulsen, Frantz; Piil, Karin
Abstract: Background: High-grade gliomas are aggressive and life-threatening brain tumors. At the time of recurrence, the patients and their families need to decide on future treatment. None of the treatment options are curative, and tradeoffs between benefits and harms must be made. This study aimed to explore the patients' and family members' decisional needs when making the decision. Methods: We performed semi-structured individual interviews with patients and family members to explore their experiences during the decision making. A phenomenological hermeneutical analysis was conducted. Results: A total of 15 patients and 14 family members aged 22-79 years participated in the study. Most of the family members were partners to the patient. The findings were centered around three interrelated and concurrently occurring themes: (I) A patient- and family-centered decision making, including the subtheme of being a supportive family member; (II) Balanced information and a trustful professional encounter; and (III) The value of hope. We found that both the patients and family members preferred to be involved in the decision making and that a trustful relationship with the surgeon, balanced and tailored information, and sufficient time to make the decision were essential. The experience of hope had a significant influence on patients' decisions. Conclusion: This study found that patient and family involvement, balanced information, and hope were the primary decisional needs of patients and family members at the time of recurrent high-grade glioma. Patients and family members can have different decisional needs, making individual needs assessment essential to decisional support.